ANALISIS MATERIAL BAJA ASTM A36 PADA DAUN PINTU AIR BENDUNG BEKASI DENGAN METODE SIMULASI BUILDING INFORMATION MODELING - Mochamad Ubaedillah Fajri; Ahsan -; Yopi Handoyo (Jurnal Ilmiah Teknik Mesin, 2018)
The operation of the intake gates of the Bulkhead Gates type weir is strongly influenced by the flowof irrigation water flow, the activity of regulating the flow rate is very important to be carried outin order to divide the amount of flow to the various regions it passes. This is generally done tomaintain the strength of the steel structure of the air intake door of the Bulkhead Gates type weir.Water flow rate with a certain capacity if there is a decrease in water flow discharge and theamount of discharge of water flow which increases dramatically in the rainy season. When theamount of water flow increases, the operation of the sluice structure experiences a very high load,the structure of the sluice has the elasticity of the material on the sluice leaves and also thesupporting steel structure. This is very risky if there is a sudden break or crack in the sluicestructure. In this research study using the Building Information Modeling (BIM) method using steelstructure modeling The intake gates of the Bulkhead Gates type weir as the basis of the research tofind the minimum and maximum loading influenced by the water flow discharge. Physically stellstructure The bulkhead gates type intake gates fulfill the loading requirements. This research usesASTM A36 Sheet Plate carbon steel material on sluice leaves which can provide accurate loadingpredictions on the simulation. a combination of variations in water level above the averagethreshold of TMA 18.98 masl with Q to SITB (m3/sec) with very heavy rainfall. BIM meodelingsimulation on the sluice gate can also effectively regulate discharge and also the threshold ofloading on the steel sluice structure. From the results of the simulation of the BIM method in thisstudy can be useful as a reference to the concept of steel structure in the building of the air intakedoor of the Bulkhead Gates type weir.